ANALISIS TINDAK TUTUR PIDATO PRESIDEN JOKOWI PADA APEC 2014 DI CINA - Edward, Edward; Hutahaean, Sorta (Universitas Lancang Kuning, 2018)
This research is entitled “the analysis of illocutionary speech act of president Jokowi in APEC, China 2014”. The research was aimed at exploring and identifying speech acts uttered by president Jokowi in his presidential speech in China, 2014. Levinson (1983) proposed that the interest of pragmatic study was based on its empirical and descriptive way. Hence, this research was aimed at exploring and identifying illocutionary forms uttered by president Jokowi in his presidential speech in China, 2014. The research shows that factors of situation, place, topic, speaker and context play significantly as important roles. The form of structure of the speech was more on representative functioning to inform and invite.